ANALISIS SINONIMI VERBA SCREAM, SHOUT, DAN YELL DALAM COCA: TINJAUAN DISTRIBUSI, KOLOKASI, DAN PROSODI SEMANTIK - Ni Made Dian Paramitha Sari (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study analyses the synonymous verbs ‘scream’, ‘shout’, and ‘yell’ using data from the Corpus of Contemporary American English (COCA) spanning the period of 1995-2019. This specific timeframe was selected to capture significant shifts in communication and technology. Although these words share a similar core meaning, this research aims to demonstrate that their usage is not entirely identical. The study focuses on the distribution, frequency, colligation, and collocation of the three verbs across different registers and time periods. A mixed-methods approach, combining quantitative and qualitative methods, was employed. The quantitative method was used to calculate word frequencies, while the qualitative method was applied to analyse concordances and collocations. The findings reveal that ‘scream’ has the highest overall frequency of use, while ‘yell’ has the lowest. All three words are predominantly used as verbs compared to other word classes. In terms of registers, ‘scream’ and ‘shout’ appear most frequently in the fiction register, whereas ‘yell’ is most common in the TV register. All three words are least used in the academic register. Regarding collocation, only ‘shout’ exhibits a positive semantic prosody, while ‘scream’ and ‘yell’ tend to have a negative semantic prosody. These findings reinforce the evidence that synonymous words possess different nuances in meaning and usage, depending on their context and communicative purpose.